Pengaruh Lokasi terhadap Keputusan Memilih Sekolah Satpam PT Caraka Sakti Utama Kabupaten Subang - Nurjanah Nurjanah; Titta Partini, Siti; Mulyani Mulyani (Jurnal Manajemen Kreatif dan Inovasi, 2026)
This study aims to analyze the effect of location on the decision to choose PT Caraka Sakti Utama Security Guard School in Subang Regency. The research was motivated by the increasing competition among security guard education and training institutions and the inconsistent findings of previous studies regarding the influence of location on institutional selection decisions. A quantitative approach with descriptive and verificative methods was employed. The population consisted of 3,542 security guard training participants, while the sample comprised 97 respondents selected using proportionate stratified random sampling based on the Slovin formula with a 5% margin of error. Data were collected through a five-point Likert scale questionnaire and analyzed using descriptive statistics and simple linear regression with IBM SPSS Statistics. The findings indicate that both the location variable and the decision to choose variable were categorized as very good, with average index scores of 4.48 and 4.43, respectively. Regression analysis produced the equation Y = 9.093 + 0.859X with a significance value of 0.000, confirming that location has a positive and significant effect on the decision to choose the institution. The coefficient of determination (R²) of 0.527 shows that location explains 52.7% of the variation in selection decisions, while the remaining 47.3% is influenced by other factors. These findings highlight the importance of accessibility, visibility, traffic conditions, parking facilities, and the surrounding environment in attracting prospective participants.